MOTIVASI KEPUTUSAN RESTRUKTURISASI KREDIT PADA MASA PANDEMI COVID-19 - Diana, Nur; R. Shauki, Elvia (Faculty of Economics and Business University of Mataram, 2023)
This study aims to answer the phenomena that motivate the decision to grant credit restructuring to MSME debtors affected by COVID-19 at Regional Development Bank X. This research approach uses a qualitative single case study method with multiple embedded unit analyses. Data were obtained from observation, documentation, and semi-structured interviews. This study uses content analysis, thematic, and constant comparison with the NVivo 12 Plus. The uniqueness of this study is evaluating the phenomenon of decision-making of credit restructuring using institutional logic. It is relevant to explain the relationship between individual behavior and institutions that can influence action. The results of the study show that symbolic carriers affect material carriers thereby triggering the coupling practice that is limited to the preparation of SOPs referring to POJK No.11/POJK.03/2020; POJK No.48/POJK.03/2020; POJK No.17/POJK.03/2020, while the decoupling practice occurred in the implementation of SOPs in deciding credit restructuring during COVID-19. There are multiple logics including the logic of routines, actors, and procedures. The competing logics are logic of procedures and actors in providing considerations and decisions on debtor eligibility and credit restructuring schemes. The logic of procedure is the dominant logic that motivates making credit restructuring decisions. The contribution of the study is more directed to regulators in designing more appropriate policies by considering organizational behavior.